Should Marginal Abatement Costs Differ Across Sectors? The Effect of Low-Carbon Capital Accumulation - Vogt-Schilb, Adrien; Meunier, Guy; Hallegatte, Stephane (World Bank, Washington, DC, 2013)
The optimal timing, sectoral distribution, and cost of greenhouse gas emission reductions is different when abatement is obtained though abatement expenditures chosen along an abatement cost curve, or through investment in low-carbon capital. In the latter framework, optimal investment costs differ in each sector: they are equal to the value of avoided carbon emissions, minus the value of the forgone option to invest later. It is therefore misleading to assess the cost-efficiency of investments in low-carbon capital by comparing levelized abatement costs, that is, efforts measured as the ratio of investment costs to discounted abatement. The equimarginal principle applies to an accounting value: the Marginal Implicit Rental Cost of the Capital (MIRCC) used to abate. Two apparently opposite views are reconciled. On the one hand, higher efforts are justified in sectors that will take longer to decarbonize, such as urban planning; on the other hand, the MIRCC should be equal to the carbon price at each point in time and in all sectors. Equalizing the MIRCC in each sector to the social cost of carbon is a necessary condition to reach the optimal pathway, but it is not a sufficient condition. Decentralized optimal investment decisions at the sector level require not only the information contained in the carbon price signal, but also knowledge of the date when the sector reaches its full abatement potential.